HYBRID ALGORITHM FOR HAND GESTURE RECOGNITION USING LOCAL GABOR FILTER AND MEL FREQUENCY CEPSTRAL COEFFICIENTS - GUPTA, SHIKHA (2013)
Hand gesture is a movement ofhands having meaning to speak, with other people. However, using hand gestures as a medium for communication requires correct recognition of indeed pose and due to this, hand gesture recognition is an active area of research in the vision community. Various algorithms are proposed for gesture recognition, but not optimally designed for accuracy. Accuracy is the most important parameter for any recognition system as compared to other significant parameters. Increase in accuracy leads to decrease in the performance of other parameters; specifically, it leads the algorithm to high complexity.